Assessing the effect of orally administered Ivermectin on viremia and shedding of porcine reproductive and respiratory syndrome virus in growing pigs under field conditions - Allison, Grant; Gauger, Phillip; Osemeke, Onyekachukwu; Lawrence, Paul (Frontiers in Veterinary Science, 2025)
Despite more than three decades of research and improved biosecurity, porcine reproductive and respiratory syndrome virus (PRRSV) still causes major economic losses to the swine industry. The continued losses, especially in growing-pig populations, prompt exploration of adjunct therapies. This longitudinal field study evaluated whether orally delivered Ivermectin (0.3 mg/kg in four two-day pulses) mitigates PRRSV in a 2,400 wean-to-market barn. Treated pens recorded numerically fewer PRRSV-positive pens during the first 17 days post-weaning, as determined by oral-fluid (OF) RT-qPCR, and lower mean log₁₀ viral copies in OF at eight of nine weekly samplings across 68 days. Serum RT-qPCR, however, revealed numerically higher viremia in treated pigs. These findings warrant further studies using better trial settings or different dosing strategies.